Civil protection for the electronic consumer from misleading advertising - Ahmed Nagy, Dr. Amal (The college of law and political science journal, 2023)
The consumer in the domain of E-commerce is the same as the consumer in thetraditional contractual process, but he/she deals here through an electronic brokerand receives through this intermediary the advertisement of the commodity andpurchases it. With the appearance of communication and information technology and themerging between them, advertising via the Internet has become one of the most